RETRACTED: Management of green risk within attaining sustainable development goals - Pimonenko Tetyana; Lyulyov Oleksii; Kwilinski Aleksy; Us Yana; Korobets Olena (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002